Are Phenoxyethanol products safe for babies? – A review of current evidences - Agrawal, Amit; Pandwar, Umesh; Pandya, Nitin (Indian Journal of Child Health, 2022)
Phenoxyethanol is used at concentrations below 1% as a preservative in cosmetic products and fixative in perfumes. Some people have reported adverse responses to phenoxyethanol on their skin. Some suggest that the test subjects’ negative reactions are the result of allergies. Nevertheless, there are claims that it’s simply a skin irritant that has varying degrees of effect on various people. In 2012, the ANSM (French National Agency of Medicine and Health Products Safety) advised against using Phenoxyethanol in cosmetics for babies’ bottoms. On a European level, this advice had not been confirmed. The purpose of this article is to discuss the potential negative effects of phenoxyethanol on newborns and infants.